Struktura organizacyjna klasztoru tarnateńskiego - Czyżewski, Bogdan Stanisław (Vox Patrum, 2022)
The Regula Tarnantensis (The Rule of Tarn) is an interesting and little-known early Christian writing. Most likely, the monastery for which it was established was located on the River Tarn in south-eastern Gaul, and the Rule itself dates back to the 6th century. This research deals with the organizational structure of the monastery, i.e. functions performed by individual monks and the scope of their tasks. The most important person in that community was the abbot who was responsible to God and people for the functioning of the entire monastery, both in spiritual and organizational terms. Important tasks were also in charge of the prior. He shared some of them with the abbot, such as correcting and disciplining the brethren. Moreover, the prior verified the candidates’ reasons for choosing religious life. The other important officials in the monastery were seniores (seniors), who, among other things, provided spiritual care for candidates for the religious community. There was also a house steward, a librarian, a gardener as well as cellarers in charge of provisions for the community. Further, the Rule lists the typical agricultural tasks of monks: plowmen, reapers, vineyard workers and shepherds.